Peningkatan Kosakata Bahasa Inggris Melalui Games Bagi Siswa SMA Negeri 1 Penebel - I Gusti Ayu Mahatma Agung; I Made Perdana Skolastika; Ni Luh Putu Tarisa Damayanti; Putu Adri Wisanta (Politeknik Negeri Cilacap, 2023)
Vocabulary is an essential element in learning English. However, many students experience problems in learning English vocabulary. One of the factors that cause student's lack of vocabulary mastery is the lack of variety in the learning methods. Therefore, this community service activity aims to improve English vocabulary mastery and foster the motivation of grade 11 students at SMAN 1 Penebel. English training using games provided a new atmosphere in class. The students seemed enthusiastic during the learning process. In addition to increasing English vocabulary, games can also develop student's ability to work in teams, train memory and concentration, and improve their English skills. The evaluation results through the Google form showed that the average score for the vocabulary quiz students worked on at the end of the training was 91.43. Based on the result, it can be concluded that the student's understanding of the vocabulary being taught is quite high.